1979
DOI: 10.1111/j.1365-3083.1979.tb03277.x
|View full text |Cite
|
Sign up to set email alerts
|

Secondary MLC Responses of Primed Lymphocytes after Selective Sensitization to Non‐HLA‐D Determinants

Abstract: Two HLA-B,D-identical siblings, who differed only for the HLA-A region because of a maternal recombinational event, were studied in primary (1 degrees) and secondary (2 degrees) mixed lymphocyte culture (MLC). The HLA-A:B recombinant child did not respond to its HLA-B,D-identical sibling in either 1 degrees or 2 degrees MLC. In the reciprocal combination the non-recombinant child responded only weakly in 1 degrees MLC but responded significantly in 2 degrees MLC to the HLA-A:B recombinant child. Thus, it was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1981
1981
1988
1988

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…DY-specific TCC displayed an unusual type of autoreactivity, being restimulated not only by autologous PBMC or B-LCL, but also by HLA-mismatched allogeneic cells. Using comparable priming conditions, similar reactivities in uncloned PLT cells have been noted previously (31), and, more recently, Martin et al . (32) have described possibly similar findings at the clonal level (32) .…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…DY-specific TCC displayed an unusual type of autoreactivity, being restimulated not only by autologous PBMC or B-LCL, but also by HLA-mismatched allogeneic cells. Using comparable priming conditions, similar reactivities in uncloned PLT cells have been noted previously (31), and, more recently, Martin et al . (32) have described possibly similar findings at the clonal level (32) .…”
Section: Discussionsupporting
confidence: 82%
“…They were found to proliferate in the presence of most stimulator cells, including PBMC from the autologous donor, GP (Fig. 7), as well as allogeneic PBMC and B-LCL (KR), and suppressive (29)(30)(31) but not helper (248-3) TCC. This is a pattern characteristic of "DY"-reactive cells.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it seems as if the PLT-technique may be a valuable tool both for the detection of heterogeneity between DP, HLA-D and HLA-DR antigens and for the identification of determinants not belonging to the series of HLA-D/DR associated DP-determinants (e.g. Wank et al 1978, Zier et al 1978, Morling et al 1980c, Shaw et al 1980, Termijtelen et al 1980).…”
Section: Discussionmentioning
confidence: 99%
“…The class I loci. An HLA-A linked locus whose gene products are responsible for the induction of very weak responses in primary MLC was reported by Eijsvoogel et al (1972) and Bijnen et al (1977), whereas Wank et al (1979) confirmed the existence of such a locus and demonstrated its stimulating capacity in secondary MLC. Furthermore, it was suggested that a determinant encoded between HLA-A and -D/DR could induce weak stimulation in primary as well as secondary MLC (Wank et al 1977).…”
Section: The Class I and Non-d/dr Class Ii Loci And Their Influenmentioning
confidence: 81%